Podejmowanie zachowań ryzykownych przez osoby o psychopatycznej strukturze osobowości = Risk behaviours of people with psychopatic personality structure - Pastwa-Wojciechowska, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The factors associated with etiology and development of psychopathic personality still form the area of intensive research performed by the representatives of various scientific disciplines. A very particular place in these deliberations is taken by the cognition of effects on physical and mental health concerning the people remaining in the relationship with psychopaths; while on the contrary, significantly less research concerns the abilities of psychopaths to achieve and use their own mental, physical and social possibilities to respond adequately to environmental challenges in the context of widely understood health.
Keywords: zachowania ryzykowne; osobowość psychopatyczna; czynniki ryzyka rozwoju; wskaźniki eksternalizacji; wskaźniki internalizacji; risk behaviours; psychopathic personality; risk factors of development; externalization rates; internalization rates